2014
DOI: 10.1177/0009922814549314
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity and Critical Thinking

Abstract: Having a greater index of suspicion for abuse may mitigate missed opportunities. With variability of medical training in child abuse, the factors we identified can be used as learning objectives for continuing medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Therefore, clinicians have a unique opportunity to identify suspected mistreatment and initiate intervention. [2][3][4][5][6][7][8] Influential research in child abuse [9][10][11][12][13][14] and intimate partner violence 15,16 has focused on health care utilization before identification, highlighting that many survivors had multiple previous visits for likely abuse-related issues, suggesting "missed opportunities" for identification and early intervention. Previous research has shown that older adults experiencing mistreatment have increased rates of emergency department (ED) use 2,5 and hospitalization 17 but have not further characterized this utilization or examined its association with mistreatment detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinicians have a unique opportunity to identify suspected mistreatment and initiate intervention. [2][3][4][5][6][7][8] Influential research in child abuse [9][10][11][12][13][14] and intimate partner violence 15,16 has focused on health care utilization before identification, highlighting that many survivors had multiple previous visits for likely abuse-related issues, suggesting "missed opportunities" for identification and early intervention. Previous research has shown that older adults experiencing mistreatment have increased rates of emergency department (ED) use 2,5 and hospitalization 17 but have not further characterized this utilization or examined its association with mistreatment detection.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to emit curiosity was noted to be beleaguered by a multitude of factors from cultural values to avoidance, fear and tension (Anderson, 2019; Burton & Revell, 2017; Crisp & Lister, 2004; Daly, 2016; Finnbogadottir & Dykes, 2012; Helm, 2013; Jackson et al, 2015; Lines et al, 2017; Mauri et al, 2015; Platt & Turney, 2014; Rouf et al, 2011; Saltiel, 2016). Both Beswick (2004) and White (1959) proffered that not seeking further information was a purposeful choice.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies specifically emphasised the importance of relationship-building with clients (Finnbogadottir & Dykes, 2012;Lazenbatt, 2010;Mauri et al, 2015;Revell & Burton, 2016;Saltiel, 2016) and how this appeared to influence the depth of information elicited. Saltiel ( 2016 Interestingly, the notion of certainty, where there appeared to be concrete clinical observations, was evident in four papers (and sometimes discussed in relation to uncertainty) (Cowley et al, 2018;Finnbogadottir & Dykes, 2012;Jackson et al, 2015;Mauri et al, 2015). Whether certainty can truly be considered a facilitator of curiosity is debatable (Revell & Burton, 2016), particularly in view of the theoretical underpinning of the concept.…”
Section: Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the importance of soft tissue injuries in terms of specificity is highlighted by the work of McMahon et al [13], who reported more than 3 million cases of child abuse in a single year that included cutaneous symptoms, making it the most recognizable symptom of abuse. Jackson et al [14] highlight the contribution to delay in abuse diagnoses via clinical inattention to soft tissue findings. Accordingly, soft tissue bruising, for example, the result capillary failure via blunt trauma [15][16][17], in any of the locations indicated by the Frequency or Specificity (Tables 2 and 3) should also be considered a significant finding.…”
Section: Discussionmentioning
confidence: 99%